Gazing into an Abyss… [Review of:] Michał Chudoliński, Mroczny Rycerz Gotham. Szkice z kultury popularnej (Kraków: TAiWPN Universitas, 2023, pp. 381) - Janek, Anna (Transfer. Reception Studies, 2024)
This review concerns Michał Chudoliński’s book Mroczny Rycerz Gotham. Szkice z kultury popularnej [The Dark Knight of Gotham. Sketches from Popular Culture], which was published in 2023 by the TAiWPN Universitas publishing house. The publication is a monographic study of the universe centreed around the character of Batman. The reviewer assesses the way in which the author has achieved the research objectives, brings the research methodology of the transmedia texts analysed closer, paying particular attention to the innovative treatment of the problem of deviance in the context of comic characters.